Hi, x^2 +(2+x)*5+46x=0 solve the quadraticHi, x^2 +(2+x)*5+46x=0 solve the quadraticHi, x^2 +(2+x)*5+46x=0 solve the quadraticHi, x^2 +(2+x)*5+46x=0 solve the quadraticHi, x^2 +(2+x)*5+46x=0 solve the


Hi, x^2 +(2+x)*5+46x=0 reexplain the quadratic

Hi, x^2 +(2+x)*5+46x=0 rereexplain the quadratic

Hi, x^2 +(2+x)*5+46x=0 rereexplain the quadratic

Hi, x^2 +(2+x)*5+46x=0 rereexplain the quadratic

Hi, x^2 +(2+x)*5+46x=0 rereexplain the quadratic

Hi, x^2 +(2+x)*5+46x=0 rereexplain the quadratic

Hi, x^2 +(2+x)*5+46x=0 rereexplain the quadratic

Hi, x^2 +(2+x)*5+46x=0 rereexplain the quadratic

Hi, x^2 +(2+x)*5+46x=0 rereexplain the quadratic

Hi, x^2 +(2+x)*5+46x=0 rereexplain the quadratic

Hi, x^2 +(2+x)*5+46x=0 rereexplain the quadratic

Hi, x^2 +(2+x)*5+46x=0 rereexplain the quadratic

Hi, x^2 +(2+x)*5+46x=0 rereexplain the quadratic

Hi, x^2 +(2+x)*5+46x=0 rereexplain the quadratic

Show further